Global trends in flipped classroom research within mathematics education over past two decade: A bibliometric analysis - Gida Kadarisma; Dadang Juandi; Darhim Darhim (IKIP Siliwangi and I-MES, 2024)
This research aims to provide a bibliometric review of trends in using flipped classrooms in mathematics learning research. This research is essential to analyze the extent of the flipped classroom research trend in mathematics learning as a reference for future research in this research. Bibliometric analysis was used to analyze and classify bibliographic data by considering inclusion and exclusion criteria. The database used was Scopus using the Bibliometrix application. The search was carried out using the keywords